Quality indicators for initial licensure and discipline in nursing laws in South Korea and North Carolina. (14th November 2013) - Kim, K.K.; Kjervik, D.K.; Foster, B.
<x xml:space="preserve">Abstract</x> Background The Korean regulatory framework of nursing licensure reflects that of the USA, but its content differs in some of the powers related to quality assurance. Aim This article compares regulatory quality indicators and describes core standards in nursing regulations that are related to both initial licensure and discipline for three groups: the National Council of State Boards of Nursing, the North Carolina and the South of Korea. Methods A descriptive, comparative law design is used to examine the differences and similarities in the quality indicators and core standards found in three documents: the National Council of State Boards of Nursing Model Act, the North Carolina Nursing Practice Act and the Korean Medical Service Act for registered nurses. Results The findings indicate that ten quality indicators and two standards appear in study objects. Although most of the quality indicators are common to all documents, some differences are found in terms of the scope of criminal background checks and the range of grounds for disciplinary action. Limitations These findings cannot be generalized in the USA because although the North Carolina nursing act was selected as an example of US nursing laws, nursing laws differ somewhat across states. Conclusions This comparative study shows a clear opportunity to develop indicators that acknowledge the important areas of competence and good moral character and how they can improve patient safety in Korea. Implications for nursing and health policy This study provides recommendations for Korean nursing legislative redesign and pointers for other jurisdictions to consider.